Tingkat Pengetahuan Penggunaan Obat Tradisional dalam Pengobatan Swamedikasi pada PKK Banjar Tegal Buah Denpasar Barat - Purnama Sari, Ni Kadek Akari; Tangkas Suwantara, I Putu; Udayana Antari, Ni Putu; Megawati, Fitria; Dewi Agustini, Ni Putu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
Treatment using traditional medicine has become integrated into Indonesian society and is used to treat health problems through self-medication. Traditional medicine is a nation's cultural heritage that needs to continue to be preserved and developed to support health development. This research aims to find out how self-medication uses traditional medicine in the PKK Banjar Tegal Buah West Denpasar. This type of research is quantitative survey research with data collection techniques using questionnaires and using a Likert scale in conducting surveys with questionnaire measuring instruments. This research was conducted from April to May 2023. The population in this study were all PKK mothers who had carried out self-medication using traditional medicine and the sample in this study was 100 respondents. The instrument used was a questionnaire sheet with 20 questions. Based on the results of research on the level of knowledge of the use of traditional medicine in 100 PKK respondents with the criteria for a good level of knowledge, 88 people (88%) while 12 people (12%) of respondents were included in the sufficient category.